2000
DOI: 10.1177/1368430200003002002
|View full text |Cite
|
Sign up to set email alerts
|

‘Social Sharedness’ as a Unifying Theme for Information Processing in Groups

Abstract: Although much of the research on small groups in social psychology has emphasized cognitive, information-processing tasks (decision-making and problem solving), only recently have groups been conceptualized as information-processing systems. Partially due to this new conceptualization, group research is on the rise, yet much of this research is discipline specific. Few attempts have been made to integrate this research to provide common themes or frameworks across disciplinary boundaries. We propose that one p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
165
1
12

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(180 citation statements)
references
References 61 publications
2
165
1
12
Order By: Relevance
“…knowledge that is known only to individual group members (for reviews see e.g. Mojzisch & Schulz-Hardt, 2006;Stasser & Birchmeier, 2003;Tindale & Kameda, 2000;Wittenbaum, Hollingshead, & Botero, 2004). As a consequence of this information pooling bias, groups consistently fail to detect the optimal solution in exactly those situations where they would have the greatest advantage over individual decision makers: hidden profiles.…”
mentioning
confidence: 99%
“…knowledge that is known only to individual group members (for reviews see e.g. Mojzisch & Schulz-Hardt, 2006;Stasser & Birchmeier, 2003;Tindale & Kameda, 2000;Wittenbaum, Hollingshead, & Botero, 2004). As a consequence of this information pooling bias, groups consistently fail to detect the optimal solution in exactly those situations where they would have the greatest advantage over individual decision makers: hidden profiles.…”
mentioning
confidence: 99%
“…There is strong theoretical agreement that shared meanings in groups come from group communication and interaction (Allard-Poesi, 1998;Goodwin & Fiske, 1994;Higgins, 1992;Krauss & Fussell, 1991;Tindale & Kameda, 2000). However, little empirical work has been done to identify more precisely what aspects of the interaction prove to be influential in the development of shared cognition.…”
Section: Group Communication and Shared Mental Modelsmentioning
confidence: 99%
“…To cite some examples, a study by Brauner (as cited in Tindale & Kameda, 2000), found that two groups with dissimilar mental models about their experimental task at the beginning of the project came to reach a large degree of convergence in their thinking 22 about the task after two group discussion sessions. Hastie and Pennington (1991) examined jurors' deliberation patterns and found that in evidence driven deliberation, jurors use group discussion to reveal differences in conclusions reached about the case and to "attempt to influence one another to reach consensus on a single group story of what happened" (p. 315).…”
Section: Group Communication and Shared Mental Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information processing in collaborative learning settings is characterized by active and conscious sharing (i.e., retrieving and explicating information), discussing (i.e., encoding and elaborating the information), and remembering (i.e., personalizing and storing the information) of valuable task-relevant information and knowledge held by each group member (Hinsz et al 1997;Tindale and Kameda 2000;Tindale and Sheffey 2002). According to the evolutionary perspective of CLT on human cognitive architecture, humans have evolved to communicate with each other and obtain most of their information from each other.…”
Section: Applying Cognitive Load Theory To Collaborative Learning: Admentioning
confidence: 99%